Genetic studies for yield and its component traits in RIL population of pearl millet (Pennisetum glaucum [L.] R. Br.) - Sathya, M, P. Sumathi, N. Senthil, S.Vellaikumar and A. John Joel* (Electronic Journal of Plant Breeding, 2014)
Pearl millet [Pennisetum glaucum (L.) R. Br., Poaceae] is an important crop of the semi-arid tropics in Africa and India. A RIL mapping population developed by crossing PT 6029 × PT 6129 was evaluated for various genetic variability parameters. Analysis of variance revealed high significant values for all the 11 characters studied. Phenotypic coefficient of variation (PCV) was higher than genotype coefficient of variation (GCV) for all the characters indicating the influence of environment on the characters. High PCV and GCV were observed for yield per plant and grain weight per ear head. The high heritability was recorded for all the traits except for days to 50% flowering, days to maturity and ear head girth. High heritability coupled with high genetic advance as per cent of mean was observed for 1000 grain weight, number of productive tillers, single ear head grain weight, single ear head weight, single plant yield and plant height. These characters were controlled by additive gene effect. Hence selection based on these characters would be effective for further pearl millet improvement programme. Transgressive segregants were observed for all the 11 traits. These could be used for yield testing apart from utilizing it as pre breeding material. The mapping population could be used for mapping of genes for important traits.